Dampak Judol terhadap Identitas Global dan Dinamika Masyarakat Modern: Perspektif Mahasiswa di Tanjung Pinang - Ridho Halomoan Simanjuntak; Claudia Amanda Purba; Muhammad Ammar Ghifari (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2026)
Online gambling has become an important phenomenon in today's society, influencing various aspects of social and cultural life. This research aims to explore the impact of online gambling on the formation of global identity and the changes occurring within modern society. Using a descriptive qualitative method, data were collected through interviews with five students in Tanjung Pinang. The findings indicate that online gambling not only alters the way people interact but also leads to shifts in social values, evident in the rise of consumerist and individualistic culture. While there are negative effects, such as addiction and a decline in the quality of social relationships, online gambling also presents opportunities in the digital economy. This study recommends the need for better regulation and educational programs to raise public awareness about the risks associated with online gambling, as well as to leverage its potential benefits. Thus, this research is expected to provide a deeper understanding of the role of online gambling in shaping global identity and the dynamics of modern society.